ASSOCIATION BETWEEN HYPOLIPIDEMIAS AND COLORECTAL CARCINOMA: Hypolipidemias and Colorectal Carcinoma - Hussain, Sameed; Syed, Abdus Samad; Samad, Fauzia Abdus; Awan, Nabeela (Pakistan Armed Forces Medical Journal, 2016)
Objective: To study association of hypolipidemias and primary colorectal carcinoma in population of patients of colorectal carcinoma presenting to Combined Military Hospital (CMH) Rawalpindi. Study Design: Case control study. Place and Duration of Study: Oncology department, Combined Military Hospital (CMH), Rawalpindi. Material and Methods: Forty one treatment naïve patients between ages of 18-75, with histologically confirmed primary colorectal carcinoma were selected and their serum lipid profile was measured after an overnight fast, from Armed Forces Institute of Pathology (AFIP). These levels were compared with 41 controls, selected from healthier population, using an unpaired T test. Frequency and percentages were computed for variables; sex, age and stage at presentation. Results: Colorectal carcinoma had significant association with triglycerides (p=0.007), total cholesterol (p=0.014) and LDL (p=0.013). Conclusion: There is an inverse relationship between serum total and LDL cholesterol, and colorectal carcinoma, implying that hypolipidemias may play a role in development of colorectal carcinoma.